The Effect of Taxes on Market Balance With Subsidies As a Moderating Variable in West Papua Province - La Ode Alisyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is quantitative research with an exploratory approach. The data used in this article is secondary data that researchers obtained from the National Strategic Food Price Information Center for West Papua Province in the last 5 years. Apart from that, researchers also received it from the Central Statistics Agency. The data used in this research was analyzed using the smart PLS 4.0 analysis tool. The result in this article show the arguments that the researcher formed and formulated in the Hypothesis formulation section, namely the Sanctions variable, can have a positive relationship and a significant influence on the Market Balance and Subsidy variables and strengthen the influence of the Tax variable on Market Balance. This can be caused because the P-Values ​​value is positive and is below the 0.05 significance level, namely 0.000 for the influence of the Tax variable on Market Balance and 0.000 for the influence of the Subsidy moderation variable on the influence of the Tax variable on the Market Balance variable. This is because taxes can influence sales prices, thus affecting demand and supply. This means that increasing taxes can increase sales prices which affect supply and demand. Taxes that are properly targeted can overcome price monopoly and increase market balance. In line with this, subsidies also have the same reason for achieving market balance. Thus, the first and second hypotheses in the research can be accepted.